Integration of Systems and Services at Centro Universitário Senac - Santo Amaro Campus Aimed at Rationalizing Water Use and Minimizing Effluent Generation - Rogati, Ivan Augusto Furini; Athiê, Alessandro Augusto Rogick; Guimarães, Debora Fernanda; da Mota Lima, César Augusto Silveira; Pinheiro, Eduardo; Patricio, Talita Thomaz (Universitas Diponegoro, 2023)
At Centro Universitário Senac - Santo Amaro Campus, several systems and services have been developed, whose integration, respecting sustainability and industrial ecology premises, promote the rationalization of water use, minimization of effluent generation, and reduction of the institution's socio-environmental impacts. With a total area of 154,000 m2, the campus's occupancy rate can reach 9,594 people/day. By installing faucets and showers with a timer and flow reducer, aiming to reduce water consumption and waste, a 30% reduction in monthly consumption was achieved. An Sewage Treatment Plant (STP) with an anaerobic UASB type stage, associated with an aerobic microbiological treatment system, processes more than 300 m3/day of effluent, treating practically 100% of the wastewater generated by the campus activities, which is converted into reuse water, subsequently used for garden irrigation, facade and floor cleaning, toilet flushing, water recharge for the air conditioning system's heat exchangers, and increasing the volume of treated water returned to the groundwater through a contaminated water treatment plant. A solar water heating system with recirculation provides hot water for kitchens and locker rooms without increasing energy and water consumption on the campus. The pool water is treated with ozone gas, more effective than chlorine and less aggressive to the environment. Education for Sustainability regularly carried out with campus users complements the integration of the systems and services offered.